2022
DOI: 10.3758/s13414-021-02407-w
|View full text |Cite
|
Sign up to set email alerts
|

The aftereffect of the ensemble average of facial expressions on subsequent facial expression recognition

Abstract: An ensemble or statistical summary can be extracted from facial expressions presented in different spatial locations simultaneously. However, how such complicated objects are represented in the mind is not clear. It is known that the aftereffect of facial expressions, in which prolonged viewing of facial expressions biases the perception of subsequent facial expressions of the same category, occurs only when a visual representation is formed. Using this methodology, we examined whether an ensemble can be repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Furthermore, the insula, as part of the salience network, is important for the rapid detection of personally relevant or otherwise significant emotional cues in the environment [ 75 , 76 , 77 ]. Our findings showing the involvement of brain regions subserving emotional processing are consistent with previous findings that emotional adaptation aftereffects were associated with high-level emotional processing [ 22 , 30 , 31 , 54 , 78 ] and that the magnitude of emotional adaptation aftereffects was positively correlated with the emotional intensity of the adapting faces [ 19 , 27 , 30 , 79 ].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the insula, as part of the salience network, is important for the rapid detection of personally relevant or otherwise significant emotional cues in the environment [ 75 , 76 , 77 ]. Our findings showing the involvement of brain regions subserving emotional processing are consistent with previous findings that emotional adaptation aftereffects were associated with high-level emotional processing [ 22 , 30 , 31 , 54 , 78 ] and that the magnitude of emotional adaptation aftereffects was positively correlated with the emotional intensity of the adapting faces [ 19 , 27 , 30 , 79 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, recognition of an expression can clearly be aided by repeated visual familiarization with the identity of the face that signals that expression. Faster detection of angry expression conveyed by familiar faces suggests an interplay between emotion and identity recognition [ 30 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…There has been a growing body of aftereffect research on information related to non-presented faces, such as imagery faces ( Ryu et al, 2008 ; Zamuner et al, 2017 ), face ensemble averages ( Ying and Xu, 2017 ; Minemoto et al, 2022b ), and the social messages or perceived personality traits of facial expressions ( Engell et al, 2010 ; Wincenciak et al, 2013 ; Prete et al, 2018 ; Witham et al, 2021 ; Minemoto et al, 2022a ). The results indicated that non-presented faces also induced the aftereffect, and they showed basically the same pattern as a realistic face.…”
Section: Discussion: the Future Of The Adaptation Paradigmmentioning
confidence: 99%
“…It is important to note that the ensemble average extracted from the face groups is not necessarily the presented face. For facial expressions, adapting to sequentially or spatially presented multiple facial expressions showed the same pattern of aftereffects as when adapting to faces of the same intensity as the average of those stimuli (Ying and Xu, 2017;Minemoto et al, 2022b). Both studies have used different individuals with facial expressions as adaptation stimuli, so the average was a different individual from each model and looked more similar to morphed faces with 35 models used as test stimuli.…”
Section: Representation Of Non-presented Facementioning
confidence: 94%